297 Awardee Talk - Metabolites in stem cell differentiation and fetal development. (5th December 2019) - Du, Min
Abstract: Fetal programming, also called developmental programming, describes the impacts of maternal nutrition and other physiological stresses on fetal development, which alters the trajectory of development with persistent effects on offspring productivity and health. During fetal development, stem and progenitor cells proliferate and differentiate into muscle cells, adipocytes and other cell types, which are regulated by epigenetic changes in key developmental genes regulating cell lineage commitments. Key metabolites including a-ketoglutarate (aKG), acetyl-CoA, and S-adenosylmethionine, are cofactors or donors needed for catalyzing epigenetic modifications, regulating stem cell differentiation. Both aKG and acetyl-CoA are metabolites in Kreb's cycle, and we found that aKG is critically required for stem cell differentiation through promoting ten-eleven translocation dioxygenase (TET)-dependent DNA demethylation and histone demethylations. Besides, aKG is a cofactor for hydroxylation of proline residues of proteins, including the hydroxylation of hypoxia-inducible factor (HIF), which destabilizes HIF and inhibits HIF signaling and angiogenesis. Furthermore, aKG is required for proline hydroxylation of collagen to regulate crosslinking and fibrogenesis. As a result, aKG availability has profound impacts of stem cell differentiation and fetal development. Through glutaminolysis, glutamine is converted to aKG, while AMP-activated protein kinase (AMPK), a master regulator of cellular metabolism, regulates mitochondriogenesis and aKG production via the Kreb's cycle. Consistently, mitochondriogenesis and oxidative metabolic transition is indispensable for stem cell differentiation. In summary, maternal nutrition and physiological conditions affect metabolites available for stem cell differentiation during fetal development, which has long-term effects on the performance of offspring.